Preparation of hemicellulose-based hydrogels from biomass refining industrial effluent for effective removal of methylene blue dye - Hu, Ningmeng (Environmental technology, 2022)
Cold caustic extraction (i.e. CCE) is an essential technique for removing hemicellulose from paper-grade pulp and thus obtaining high-purity dissolving pulp in pulp and paper industry. The generated wastewater from the CCE process contains large amounts of valuable hemicellulose which should be properly treated in a cost-effective way. Therefore, in this research, the hemicellulose has been used as a raw material for preparing hemicellulose-graft-polyacrylamide (hemi-g-pAAm) hydrogel particles for efficiently adsorbing methylene blue (MB) from aqueous solutions. The mass transfer kinetic behaviours of hemicellulose during a multiple CCE process were also studied. The MB adsorption kinetic test results showed that the removal efficiency can be higher than 90% for the simulated wastewater containing 500 mg/L of MB. Of note, the maximum removal capacities for the wastewater samples containing 500 and 1000 mg/L of MB could be reached up to ∼1800 and ∼2300 (mg/g) respectively with the equilibrium time of ∼40 min. Compared to other reported materials, the superior adsorption performance of the prepared hemicellulose-based hydrogel proved its great potential for application in the wastewater treatment of dye industry